Teacher's Perspective on STEAM Life Skills-Based Learning as a Means of Strengthening Pancasila Student Profiles - Roshayanti, Fenny; Purnamasari, Veryliana; Wijayanti, Arfilia (KnE Social Sciences, 2022)
The STEAM approach contains life skills that support the development of project-based learning, which strengthens the profile of Pancasila students, so it is hoped teachers can implement STEAM life skills-based learning. This research aims to learn the perspective of teachers on STEAM life skills-based learning. The subjects of this study are 125 teachers from Central Java. The data collection technique used was a questionnaire, with data analysis carried out using the Milles and Huberman (2007) model. The results showed that 32.1% of teachers stated “strongly agree”,” and 42.9% of teachers stated “agree” when asked if they had heard of the STEAM approach; only 4% of teachers stated, “strongly disagree.” This shows that most teachers have heard about STEAM and have a fairly high level of understanding of the benefits of STEAM life skills-based classroom learning. Keywords: STEAM-based learning, life skills, Pancasila Student Profile